Narwhal (Monodon monoceros) detection by infrared flukeprints from aerial survey imagery. Issue 8 (9th August 2021) - Florko, Katie R. N.; Carlyle, Cody G.; Young, Brent G.; Yurkowski, David J.; Michel, Christine; Ferguson, Steven H.
Abstract: Visual and observer aerial surveys are important for monitoring wildlife populations but are subject to visibility biases where animals may go undetected. The use of infrared technology in aerial surveys has the potential to reduce visibility biases, both when recording data and in the retrospective processing of the footage, and thus complements visible wavelength photography. We used infrared video during marine mammal surveys in the high‐Arctic and indirectly detected narwhal ( Monodon monoceros ) via their thermal flukeprints (i.e., thermo‐stratified water mixing from fluke strokes). This novel indicator persisted for a longer duration than when the animal was at the water's surface, which likely improved the probability of an animal being observed by increasing the duration of its detectability. Using infrared to complement aerial photographic surveys may assist in monitoring whales, especially in remote areas. Our results highlight how infrared technology may be used to develop automatic detection and remote‐monitoring methodology.